On the balanced elementary symmetric Boolean functions - Qu, Longjiang (2014)
In this paper, we give some results towards the conjecture that σ2t+1l-1,2t are the only nonlinear balanced elementary symmetric Boolean functions where t and l are positive integers. At first, a unified and simple proof of some earlier results is shown. Then a property of balanced elementary symmetric Boolean functions is presented. With this property, we prove that the conjecture is true for n=2m+2t-1 where m,t(m>t) are two non-negative integers, which verified the conjecture for a large infinite class of integer n.